2007
DOI: 10.1109/iembs.2007.4353494
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of EEGs in Alzheimer's Disease using Information Theoretic Methods

Abstract: The number of people that now go on to develop Alzheimer's disease (AD) and other types of dementia is rapidly rising. For maximum benefits from new treatments, the disease should be diagnosed as early as possible, but this is difficult with current clinical criteria. Potentially, the EEG can serve as an objective, first line of decision support tool to improve diagnosis. It is non-invasive, widely available, low-cost and could be carried out rapidly in the high-risk age group that will develop AD. Changes in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 8 publications
2
28
0
1
Order By: Relevance
“…As pointed out earlier, several studies have investigated whether the complexity of EEG signals is perturbed by MCI or AD [77,82,87,88,89,90,91,92,93,94,95]. The following measures have been applied in this context: approximate entropy [87,88,89,90], sample entropy [87,94], Tsallis entropy [82], multiscale entropy [87,95], auto-mutual information [77,87,88], Lempel-Ziv complexity [87], universal compression [82], fractal dimension [91], correlation dimension [92,93], and largest Lyapunov exponent [93].…”
Section: Overview Of Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As pointed out earlier, several studies have investigated whether the complexity of EEG signals is perturbed by MCI or AD [77,82,87,88,89,90,91,92,93,94,95]. The following measures have been applied in this context: approximate entropy [87,88,89,90], sample entropy [87,94], Tsallis entropy [82], multiscale entropy [87,95], auto-mutual information [77,87,88], Lempel-Ziv complexity [87], universal compression [82], fractal dimension [91], correlation dimension [92,93], and largest Lyapunov exponent [93].…”
Section: Overview Of Resultsmentioning
confidence: 99%
“…The parameter q is a measure of the non-extensitivity of the system of interest: the Tsallis entropy of two independent systems is in general not equal to the sum of the Tsallis entropies of those systems; only when q = 1 the Tsallis entropy of two independent systems is equal to the sum of the Tsallis entropies of those systems, as expected for an extensive system. In [82] the Tsallis entropy of EEG signals is determined by quantizing the amplitude of the EEG; Tsallis entropy is computed from the histogram of amplitude values (with q = 0.5, for the sake of definiteness). Approximate entropy [73] reflects the likelihood that patterns in a given signal will not be followed by additional "similar" patterns.…”
Section: Review Of Complexity Measuresmentioning
confidence: 99%
“…Information theoretic methods (i.e., TsEn and LZC) have emerged as a potentially useful complexity-based approach to derive robust EEG biomarkers of AD [47,[58][59][60][61][62]. They are attractive because of the potential natural link between information theory-based biomarkers and changes in the brain caused by AD [58]. Conceptually, information processing activities in the brain are thought to be reflected in the information content of the EEG.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we investigated an important class of complexity measures, information theoretic methods, which offers a potentially powerful approach for quantifying changes in the EEG due to AD [58]. Information theoretic methods (i.e., TsEn and LZC) have emerged as a potentially useful complexity-based approach to derive robust EEG biomarkers of AD [47,[58][59][60][61][62]. They are attractive because of the potential natural link between information theory-based biomarkers and changes in the brain caused by AD [58].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, different kinds of entropic algorithms have been applied to the analysis of EEG signals of healthy subjects during resting states or cognitive tasks, epilepsy and Parkinson's disease. 9,10 Furthermore, several entropic studies [11][12][13][14][15][16][17] have all shown that the EEG of AD patients seems to be less complex than that of age-matched control subjects.…”
Section: Introductionmentioning
confidence: 98%